A Rare Case of Bilateral Tubal Ectopic Pregnancy Following Intracytoplasmic Sperm Injection-Embryo Transfer (ICSI-ET) - Ferruh Acet; Ege Nazan Tavmergen Goker; Ismet Hortu; Gulnaz Sahin; Erol Tavmergen (Revista Brasileira de Ginecologia e Obstetrícia, 2020)
Abstract Bilateral tubal ectopic pregnancy is a very rare form of ectopic pregnancy. The incidence is higher in women undergoing assisted reproductive techniques or ovulation induction. We report the case of bilateral tubal ectopic pregnancy. The patient was 30 years old and had a 3-year history of infertility; she was referred to the in-vitro fertilization (IVF) program because of tubal factor infertility. A pregnancy resulted from the transfer of two embryos during an artificial cycle. Despite the increase in β-hCG values during the follow-up, 22 days after the embryo transfer, the β-hCG levels were 2,408 U/L and the serum progesterone (P4) level was 10.53 ng/ml. After application with methotrexate, β-hCG levels did not decrease effectively. Moreover, the sonographic screening revealed a suspicious bilateral tubal focus for ectopic pregnancy. A mini-laparotomy was performed and a bilateral tubal pregnancy was found. In the case of unilateral tubal pregnancy after the transfer of two embryos, the situation of the other tube should be systematically checked and β-hCG levels should be monitored.